10.1002/9781118797914 (CrossRef Listing of Deleted DOIs, 2000)
Universal Health Coverage (UHC) aims to ensure equitable access to quality healthcare without financial hardship. Somalia presents a critical test case for UHC implementation in fragile and conflict-affected settings due to decades of state collapse, weak governance, and heavy reliance on an unregulated private health sector. This commentary examines Somalia's policy paradox: the coexistence of formal commitment to UHC alongside a predominantly market-driven, donor-dependent, and weakly regulated healthcare system. Drawing on evidence from Somalia and comparable low-income settings, the article argues that unregulated privatization structurally undermines equity, financial protection, and quality of care. High out-of-pocket expenditure, fragmented governance, weak regulatory oversight, urban-rural disparities, and donor-driven financing continue to impede progress toward universal and equitable healthcare access. Although private providers remain indispensable in Somalia's current context, market expansion alone cannot achieve UHC without effective state stewardship, pooled financing mechanisms, and robust regulatory institutions. The commentary concludes that Somalia's pathway toward UHC depends on transitioning from an unregulated commercialized health market toward a regulated mixed health system grounded in equity, accountability, and public-sector governance.